Antifungal and Antioxidant Therapy for the Treatment of Fungal Infection with Microemulsion Gel Containing Curcumin and Vitamin C - Dubey, Akhilesh (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: Fungal infection on the skin is one of the common dermatological diseases especially for the people living in hot and humid climatic conditions. Conventional topical formulations suffer from its own limitations such as lack of site-specific delivery, drug bioavailability, and patient compliance. Curcumin oil was selected as bioactive molecules which target fungal infection which also act as an oil phase for microemulsion preparation. Another strategy was implemented in this research study was to protect the skin from excessive exposure from free radicals by supporting the skin endogenous antioxidant system by adding ascorbic acid (Vitamin C) as an adjunct. Materials and Methods: Micro emulsion gel was formulated with curcumin oil as an active ingredient as well as an oil phase along with ascorbic acid as an adjunct (antioxidant), tween 20, and isopropanol as surfactant and cosurfactant, respectively. Carbopol 940 was chosen as a polymer for the preparation of gel. Pseudoternary phase diagram of microemulsion with various surfactant/cosurfactant ratios (1:1–4:1) were constructed to study the phase behavior. Minimum inhibitory concentration study and Fourier transform infrared (FTIR) study was conducted to check antifungal activity and possible drug-excipient interactions, respectively. The developed formulations were characterized for physicochemical parameters such as globule size, zeta potential, viscosity, pH, etc. The optimized microemulsion formulations were further loaded into the carbopol gel base and evaluated. Results: Surfactant/cosurfactant weight ratio 3:1 was found to be largest in the percentage area of micro emulsion region. FTIR study did not show any potential drug-excipient interaction and curcumin oil showed considerably greater antifungal activity as compared to clotrimazole. The physical appearances of all the formulations were found to be yellowish, transparent, clear, glossy, and consistent. The pH, viscosity, droplet size of all the formulations was found to be in the acceptable range. From the results of in vitro drug release, approximately 90% of drug released was noted at the end of 10 h and ex vivo release study showed possible permeation mechanism of drug. In vitro antioxidant activity showed that microemulsion gel containing ascorbic acid possess significant free radical scavenging activity in a concentration-dependent manner. In vivo study showed that microemulsion gel containing curcumin oil and ascorbic acid has significant antifungal and antioxidant effect. Conclusions: Curcumin oil was successfully incorporated into topical microemulsion gel prepared with Vitamin C used as an adjunct and showed good spreadability, viscosity, drug release, in vitro antioxidant activity, and in vivo antifungal activity.